Simulation of flapping wing - Liong, Sun Loon. (2013)
This research’s objective is to present the application of Reynolds Stress Model (RSM) for evaluating the performance of flapping wing aerodynamic using Fluent. It also made a detail investigation on the parameters that influence the airfoil during the oscillating movement. The investigation begins with validating flow domain and turbulence model on stationary airfoil against unrealistic solution. After gaining confidence in stationary case, the investigation is extended to oscillating airfoil. The result suggests that the maximum propulsive efficiency exist at specific Stroudal Number. The interrelation oflift and thrust force to frequency is established.